Coordinated beamforming design in downlink multi-cell multi-user wireless networks - Pei-zhong XIE; Bao-yu ZHENG; Wen-jing YUE (Tongxin xuebao)
To obtain the good sum-rate performance in multi-cell multi-user wireless networks with frequency reuse,coordinated beamforming design problem of co-channel interference mitigation was studied.Theoretical analysis results with the game theory show that,the collaborative beamforming vector of the optimal performance is a linear combination of selfishness and altruism strategy.A beamforming vector iteration algorithm to maximize sum-rate was presented,and estimation method about composite coefficient based on the statistic of channel state information was proposed.Finally， the results of simulation assess the performance of the algorithm and show convergence of the proposed algorithm.